Climate change and mental health: time for action and advocacy. (24th March 2023) - Power, Emmet; McCarthy, Niamh; Kelly, Ina; Cannon, Mary; Cotter, David
Abstract: Climate change poses an existential threat to our planet and our health. We explore the intersections of climate change and mental health which has been under-recognised to date. Climate change can affect mental health directly through the effects of extreme weather events such as heat, drought and flooding, and indirectly through increasing rates of migration and inequality. Vulnerable individuals with neuropsychiatric disorders will be particularly at risk. Emerging evidence is also showing effects of air pollution on brain development. Mitigation efforts related to reducing carbon emissions will have both direct and indirect effects on mental health. A further consideration demonstrated by the COVID-19 pandemic is that the spread of infectious disease can have substantial effects on the mental health of the population. With climate change and biodiversity loss, pandemics could recur in the future with increasing frequency. It is now essential that mental health professionals be equipped as agents for climate action.